Dinitrogen Activation by Tricoordinated Boron Species: A Systematic Design. Issue 3 (14th January 2020) - Rouf, Alvi Muhammad; Dai, Chenshu; Xu, Fangzhou; Zhu, Jun
Abstract: Molecular nitrogen (N2 ), an abundant component of the atmosphere, is appealing for industrial value‐added products. However, its intrinsic inertness limits its activation to mainly metallic species. Environmental concerns and harsh reaction conditions have resulted in a demand for alternate nonmetallic and nontoxic routes to activate and functionalize N2 at ambient conditions. Comprehensive density functional theory (DFT) calculations are performed on N2 activation by boron species, specifically for the experimentally more accessible tricoordinated boron compounds. Subsequently designed frustrated Lewis pairs (FLPs) combining screened N ‐heterocyclic carbene with boron moieties can make N2 activation both kinetically and thermodynamically favorable, displaying high potential for metal‐free N2 activation. The significant thermodynamic stability of the products stabilized by aromaticity and low activation barriers could be a breakthrough for the development of FLP chemistry on metal‐free N2 activation. Abstract : Dinitrogen activation is predicted to be thermodynamically and kinetically favorable through a realistic metal‐free frustrated Lewis pair (FLP) designed systematically from tricoordinated boron and N ‐heterocyclic carbene species. The significant thermodynamic stability of the products stabilized by aromaticity and low activation barriers could be a breakthrough for the development of FLP chemistry on metal‐free N2 activation.